Prevention of the Corruption Crime through Administrative Enforcement Mechanism against Abuse of Authority - Wahbi Rahman; Sudarsono Sudarsono; Prija Djatmika; Abdul Madjid; Ramalinggam Rajamanickam (Journal of Law and Legal Reform)
The law regulates that abuse of authority that results in state financial losses is a criminal offence of corruption. Law 30 of 2014 concerning Government Administration regulates the accountability mechanism for discretion that falls into the category of abuse of authority which then causes state losses which can lead to the application of administrative sanctions as stipulated in Article 80 paragraph (4) of the Government Administration Law. Based on this, the researcher draws a theoretical problem regarding the Prevention of Corruption Through Administrative Enforcement Mechanisms against Abuse of Authority in the Form of Discretion that causes state financial losses using normative juridical legal research methods with a focus on discussions related to the application of systematic specialist principles in cases of abuse of authority that cause state financial losses as a concept. Where based on the research that has been carried out, it is known that with the development of applicable legal instruments, administrative enforcement against abuse of authority in the form of discretion that causes state financial losses can be used as an instrument to prevent the occurrence of a criminal act of corruption by using the principle that does not override each other,  meaning that if it can be resolved by administrative instruments then criminal law instruments are no longer applied, which is theoretically called the principle of Una-Via or ultra vires, meaning that if a case has been resolved administratively then the opportunity to resolve the case by other legal means is closed.